Identification of Problems of Soybean Growers in Madhya Pradesh - Dupare, B.U.; Billore, S.D.; Joshi, O.P. (Indian Journal of Extension Education, 2009)
A study to delineate the major problems faced by the soybean growers of Madhya Pradesh was undertaken during the organization of the Western Regional Agricultural Fair- cum- Exhibition-2007 sponsored by Department of Agricultural and Cooperation, Ministry of Agriculture, Government of India at National Research Centre for Soybean. It brought out that non- availability of quality seed improved varieties of Soybean is the major problem experienced by the farmers. The problem associated with management of insect-pests and disease complex followed the suit. Among the pests, girdle beetle and the green semilooper were found to be more responsible for the yield loss in farmers field. Resorting to imbalanced fertilization and untimely availability of needed fertilizers ranked third, while the marketing and infrastructure related bottleneck was ranked fourth among the major problem identified.